2022
DOI: 10.1371/journal.pdig.0000052
|View full text |Cite
|
Sign up to set email alerts
|

Real-time estimation of the epidemic reproduction number: Scoping review of the applications and challenges

Abstract: The time-varying reproduction number (Rt) is an important measure of transmissibility during outbreaks. Estimating whether and how rapidly an outbreak is growing (Rt > 1) or declining (Rt < 1) can inform the design, monitoring and adjustment of control measures in real-time. We use a popular R package for Rt estimation, EpiEstim, as a case study to evaluate the contexts in which Rt estimation methods have been used and identify unmet needs which would enable broader applicability of these methods in real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…EpiEstim is a powerful tool to estimate in real-time and is probably the best tool currently available to deliver timely estimates of the reproduction number [ 41 ]. EpiLPS can be considered a real-time approach only to a certain degree, where the real-time concept is partially present but fundamentally different from the one proposed in EpiEstim.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EpiEstim is a powerful tool to estimate in real-time and is probably the best tool currently available to deliver timely estimates of the reproduction number [ 41 ]. EpiLPS can be considered a real-time approach only to a certain degree, where the real-time concept is partially present but fundamentally different from the one proposed in EpiEstim.…”
Section: Resultsmentioning
confidence: 99%
“…EpiEstim is a powerful tool to estimate R t in real-time and is probably the best tool currently available to deliver timely estimates of the reproduction number [41]. EpiLPS can be Table 4.…”
Section: Real-time Considerationsmentioning
confidence: 99%
“…delay distributions and ascertainment rates), and are much more computationally intensive, which can be a barrier to the adoption of such methods by users. 14 Here, Rt estimates are based on a single daily incidence reconstruction, meaning Rt can be estimated very rapidly from aggregated data, which is particularly desirable during real-time outbreak analysis. 14 A potential downside is that uncertainty in Rt estimates could be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…14 Here, Rt estimates are based on a single daily incidence reconstruction, meaning Rt can be estimated very rapidly from aggregated data, which is particularly desirable during real-time outbreak analysis. 14 A potential downside is that uncertainty in Rt estimates could be underestimated. However, the simulation study showed that the 95% credible interval of estimates encompassed the correct value of Rt the majority of the time, and we found no substantial indication that this approach detrimentally affected our characterisation of the uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation